2016
DOI: 10.1186/s40064-016-3625-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analyses of the novel chimeric hemostatic agent generated via nanotechnology, ABS nanohemostat, at the renal tissue level

Abstract: Ankaferd Blood Stopper (ABS), a hemostatic agent of plant origin, has been registered for the prevention of clinical hemorrhages. Currently there is no data regarding the ultrastructural analysis of ABS at the tissue level. The aim of this study is to assess renal tissue effects via scanning electron microscopy (SEM) analyses for the ABS and ABS nanohemostat (formed by the combination of self-assembling peptide amphiphile molecules and ABS). SEM experiments were performed with FEI Nova NanoSEM 230, using the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Studies conducted on the pollen morphology of the T. camphoratus complex using Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) also confirmed that there are different taxa grouped together (Zavada and Lowrey, 2010). The use of Scanning Electron Microscopy to study the micromorphology of eukaryotes including plants has proven useful as a tool to resolve many taxonomic uncertainties (Huri et al, 2016). Therefore, micromorphological studies were more useful in distinguishing between the two species than the macromorphological study.…”
Section: Morphology Studymentioning
confidence: 97%
“…Studies conducted on the pollen morphology of the T. camphoratus complex using Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) also confirmed that there are different taxa grouped together (Zavada and Lowrey, 2010). The use of Scanning Electron Microscopy to study the micromorphology of eukaryotes including plants has proven useful as a tool to resolve many taxonomic uncertainties (Huri et al, 2016). Therefore, micromorphological studies were more useful in distinguishing between the two species than the macromorphological study.…”
Section: Morphology Studymentioning
confidence: 97%
“…SLac loaded with bactretase produced a kind of drug-loaded hydrogel named SB50, which enhanced the role of coagulation. Huri, Dogantekin et al (2016) mixed ABS hemostatic agent with amphiphilic short peptide (Lauryl -VVAGK-Am) 1:1 to obtain a kind of nano hemostatic agent, which played an excellent hemostatic role in partial nephrectomy.…”
Section: Hemostatic Strategies In Biomaterialsmentioning
confidence: 99%